2004
DOI: 10.1161/01.cir.0000127958.21003.5a
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of the Interleukin-1 Receptor Family Member ST2 Predict Mortality and Clinical Outcome in Acute Myocardial Infarction

Abstract: Background-Mechanically overloaded cardiomyocytes secrete a soluble interleukin-1 receptor family member called ST2. Serum levels of ST2 are associated with prognosis in nonischemic heart failure, but the predictive value of ST2 in patients with acute myocardial infarction is unknown. In an analysis of outcomes at 30 days by ST2 quartiles, both death (Pϭ0.001) and the combined death/heart failure end point (Pϭ0.001) showed a significant graded association with levels of ST2; furthermore, in-hospital death (Pϭ0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
250
3
21

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 374 publications
(286 citation statements)
references
References 21 publications
(22 reference statements)
12
250
3
21
Order By: Relevance
“…Circulating sST2 was previously identified as a prognostic marker in heart failure and myocardial infarction 7, 8, 9, 24. Together with other cardiac biomarkers such as troponin25 and B‐type natriuretic peptide (BNP),26, 27 our data highlight overlapping injury responses that occur following both cerebrovascular and cardiovascular injury.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Circulating sST2 was previously identified as a prognostic marker in heart failure and myocardial infarction 7, 8, 9, 24. Together with other cardiac biomarkers such as troponin25 and B‐type natriuretic peptide (BNP),26, 27 our data highlight overlapping injury responses that occur following both cerebrovascular and cardiovascular injury.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies have identified sST2 as a prognostic biomarker in cardiovascular disease 7, 8, 9. In order to exclude the possibility that the association between sST2 and outcome was related to underlying cardiovascular disease, we developed sequential multivariable models that included cardiovascular disease risk factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…sST2 levels were measured in serum from 810 patients in the Thrombolysis In Myocardial Infarction (TIMI) 14 study (362 patients) and the TIMI-23 study (448 patients); both compared different anticoagulation strategies in patients after acute MI with ST segment elevation [46]. Baseline levels of sST2 were significantly higher in patients who died or developed congestive HF within 30 days.…”
Section: Sst2 and Hf Diagnosis And Prognosismentioning
confidence: 99%
“…135 IL-33/ST2 signalling is a mechanically activated, cardioprotective fibroblast-cardiomyocyte paracrine system. 136,137 ST2 is elevated following myocardial infarction 138 and elevated levels predict an adverse outcome independently of NTproBNP. 139 The role appears to be predominantly prognostic, 140 but a role in the emergency department population has been questioned, 141 as has the concept of additional risk prediction over current markers.…”
mentioning
confidence: 99%